Congenital lobar emphysema - Rosa, Folco; J. Reissenweber, Nelson; Mañe Garzon, Fernando (Cirugía del Uruguay, 1971)
A case of lobar emphysema in a 10 day old infant is described. The upper left pulmonar lobule was affected as demonstrated by clinical and radiological signs. After lobectomy all sypmtoms subsided and the present condition status of the child is excellent. The anatomical study showed a marked reduction of the mesodermic complex throughout the bronchial tree of the affected lobule (car ilage, smooth muscle and elastic fibers. Each bronchial ramification is similar to another which is placed more periferically in a normal lung. The increase of collagen fibers in interlobulillar septa and the presence of abnormal macrophages with haemosiderine suggest that the process of pulmonar insufflation began "in utero", since 10 days are not sufficient to bring about such changes.